Automatisierte Entscheidungsfindung mittels großer Sprachmodelle (LLM) im Beschäftigtenkontext – Interview mit einem Chatbot - Kätscher, Johannes; Pesch, Paulina Jo (Künstliche Intelligenz und Recht, 2024)

Bitcoin: A first legal analysis with reference to German and US-American law - Boehm, Franziska; Pesch, Paulina Jo (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2014)
The use of Bitcoins is increasing rapidly. Bitcoins are utilized in ecommerce to purchase both legal and illegal goods, they are transferred and traded and companies have invested their capital in the new digital currency. While the technical aspects of the system are well established, the legal framework remains unclear. Legislators all over the world are just starting to discover this new virtual phenomenon. This article illustrates selected legal challenges arising in different fields of law (public, criminal and civil law). Particular attention is paid to the German situation while the US-American context is also considered.
CRIS-Team Scopus Importer:2023-10-09

Cheat happens – Grenzen des Umarbeitungsrechts an Software (Anmerkung zu EuGH, Urteil vom 17.10.2024 – C-159/23 – Sony Computer/Datel Design (ZUM 2025, 115) - Pesch, Paulina (Zeitschrift für Urheber- und Medienrecht, 2025)
Die Entscheidungsanmerkung skizziert die Entscheidung des EuGH in Sachen Cheatsoftware sowie die wichtigsten Fakten des Falls. Es erklärt und kommentiert dann die Entscheidung, analysiert ihre Reichweite und weist auf offene Fragen hi

COnSeNT 2022: 2nd International Workshop on Consent Management in Online Services, Networks and Things - Pesch, Paulina J.; Pandit, Harshvardhan J.; Jesus, Vitor; Santos, Cristiana (WWW 2022 - Companion Proceedings of the Web Conference 2022, 2022)
CRIS-Team Scopus Importer:2023-10-09
Keywords: consent; legal compliance; privacy; user-agents; web

Cryptocoin-Schulden – Haftung und Risikoverteilung bei der Verschaffung von Bitcoins und Alt-Coins - Pesch, Paulina (C.H.Beck, 2017)
Die Nutzung von Bitcoin und anderen Cryptocoin-Systemen nimmt stetig zu. Die dezentralen Systeme ermöglichen ihren Nutzern direkte Online-Transaktionen. Der Blockchain als zugrunde liegender Infrastruktur wird als Grundlage auch komplexerer Systeme mit erweitertem Funktionsumfang erhebliche Innovationskraft und ökonomische Relevanz beigemessen. Zugleich herrscht noch beträchtliche Rechtsunsicherheit selbst bei grundlegenden vertragsrechtlichen Fragen dezentraler Cryptocoin-Transaktionen: Handelt es sich bei Cryptocoins um Geld? Welche spezifischen Risiken sind mit den Transaktionen verbunden? Welche Partei haftet bei dem Verlust von Cryptocoins oder der Verzögerung einer Transaktion? Grundlage für die Beantwortung der aufgeworfenen Fragen bildet eine profunde Darstellung der technischen Funktionsweise und tatsächlichen Nutzung von Bitcoin als relevantestem Vertreter der untersuchten Cryptocoin-Systeme. Sodann widmet sich das Werk der Frage, auf welche Cryptocoin-bezogenen Verträge deutsches Recht Anwendung findet. Der Fokus der Abhandlung liegt auf der vertragsrechtlichen Haftung und Risikoverteilung bei Cryptocoin-Transaktionen. Vorab wird untersucht, ob Cryptocoins sich in die klassischen Kategorien von Rechtsgegenständen einordnen lassen. Den Schwerpunkt bildet dabei die Frage, ob Cryptocoins als Geld begriffen werden können. Stimmen in der Literatur, die eine Erfüllung von Geldfunktionen durch Bitcoins und Alt-Coins annehmen, wird eine fundierte ökonomische Analyse der Systeme vor dem Hintergrund ihrer technischen Eigenschaften und ihrer realen Nutzung entgegengesetzt. Schließlich werden die spezifischen Risiken von Cryptocoin-Transaktionen herausgearbeitet und auf dieser Grundlage die Haftung und Risikoverteilung der beteiligten Parteien entwickel
Keywords: Bitcoin; Cryptocoin; Blockchain; Kryptowährung; Vertragsrecht

Drivers and Obstacles for the Adoption of Consent Management Solutions by Ad-Tech Providers - Pesch, Paulina Jo (Proceedings - 2021 IEEE European Symposium on Security and Privacy Workshops, Euro S and PW 2021, 2021)
In the world of online marketing, Consent Management Providers (CMPs) are on the rise. CMPs collect online users' consent to the processing of their personal data by publishers and ad-Tech vendors. At the same time, there are reasonable doubts about the compliance of the existing market standard with the General Data Protection Regulation (GDPR). This could potentially create compliance risks for the companies adopting the standard, in particular for ad-Tech vendors that-in the pre-CMP era-were invisible to users.This paper reveals drivers and obstacles for the adoption of the Transparency Consent Framework (TCF) by ad-Tech-vendors, gained in semi-structured interviews with representatives of Global Vendors List (GVL) members. Presenting the first qualitative study of ad-Tech vendors' perspectives, the paper provides novel insights into the CMP ecosystem. It particularly shows existing market pressure and reveals ad-Tech vendors' confusion and doubts about the TCF's compliance with the GDPR.
CRIS-Team Scopus Importer:2023-10-09
Keywords: ad-Tech vendors; CMPs; Consent management; cookies; GDPR; online advertising; TCF

LLMs im Forschungsdatenschutz – Rechtmäßigkeit der Nutzung und des Finetunings von LLMs zu wissenschaftlichen Forschungszwecken - Pesch, Paulina; Magnussen, Kristina (Datenschutz und Datensicherheit, 2025)
Bei der automatisierten Generierung von Texten erzielen vortrainierte Large Language Models (LLMs) wie GPT-4o, Claude, DeepSeek oder Llama oft zufriedenstellende Ergebnisse. In vielen Bereichen, z. B. bei der Bearbeitung komplexer juristischer Aufgaben, ist die Leistung solcher LLMs aber noch unzureichend. Bessere Ergebnisse versprechen domänenspezifische LLMs. Diese sind speziell für bestimmte Einsatzzwecke und -bereiche trainiert, in aller Regel, indem vortrainierte LLMs beim sog. Finetuning mit domänenspezifischen Daten nachjustiert werden. So kann man etwa LLMs zur Generierung von Entwürfen für gerichtliche oder behördliche Entscheidungen, Gutachten oder Schriftsätze[1] durch ein Finetuning mit entsprechenden Texten entwickeln. Das Training und die Nutzung von LLMs werfen aber praktische und rechtliche Probleme auf. Inwiefern sich LLMs als nützlich erweisen und datenschutzkonform betreiben lassen werden, ist noch weitgehend ungeklärt. Die Ergebnisse von Experimenten mit vortrainierten LLMs lassen sich nicht einfach auf andere, erst recht nicht auf domänenspezifische LLMs übertragen. Daher besteht insofern erheblicher Forschungsbedarf. Forschungseinrichtungen, Wissenschaftlerinnen oder Unternehmen, die zu Forschungszwecken mit LLMs experimentieren oder diese finetunen, müssen die damit verbundenen, auf personenbezogene Daten bezogenen Verarbeitungsvorgänge datenschutzkonform gestalten. Für entsprechende Forschungsprojekte empfehlen sich stets datenschutzrechtliche Ausführungen im Projektantrag, die Einbindung von Datenschutzexpertise im Projektteam sowie die Benennung einer Datenschutzbeauftragten. Der Beitrag bietet einen Überblick über grundlegende Datenschutzfragen der LLM-Forschung und damit eine Orientierungs- und Argumentationshilfe für die Begründung und Sicherstellung der Rechtmäßigkeit von Forschungsarbeiten. Er beschränkt sich auf Datenverarbeitungen zu Forschungszwecken. Keinesfalls dürfen durch Forschungsprojekte höhere Datenschutzanforderungen an die Entwicklung und den Betrieb von LLMs in der Praxis umgangen werden. Sollen in der Forschung entwickelte LLMs in Produkte oder Dienstleistungen integriert werden, ist dies von vornherein datenschutzrechtlich zu bedenken und verbietet sich insoweit der Rückgriff auf Normen, die wissenschaftliche Forschung privilegiere
Keywords: Large Language Models; LLMs; KI: Künstliche Intelligenz; Training; Finetuning; DSGVO; Forschungsdatenschutz; Rechtsgrundlage; berechtigtes Interesse; besondere Kategorien personenbezogener Daten; Verantwortlichkeit

Messung der Datenminimierung für den Beschäftigtendatenschutz am Beispiel von Standortdaten - Schleper, Janine; Kohn, Matthias; Pesch, Paulina Jo; Waldmann, Ulrich; Kunz, Thomas (Lecture Notes in Informatics (LNI), Proceedings - Series of the Gesellschaft fur Informatik (GI), 2022)
CRIS-Team Scopus Importer:2023-10-09

Potentials and Challenges of Large Language Models (LLMs) in the Context of Administrative Decision-Making - Pesch, Paulina (European Journal of Risk Regulation, 2025)
Large Language Models (LLMs) could facilitate both more efficient administrative decision-making on the one hand, and better access to legal explanations and remedies to individuals concerned by administrative decisions on the other hand. However, it is an open research question of how performant such domain-specific models could be. Furthermore, they pose legal challenges, touching especially upon administrative law, fundamental rights, data protection law, AI regulation, and copyright law. The article provides an introduction into LLMs, outlines potential use cases for such models in the context of administrative decisions, and presents a non-exhaustive introduction to practical and legal challenges that require in-depth interdisciplinary research. A focus lies on open practical and legal challenges with respect to legal reasoning through LLMs. The article points out under which circumstances administrations can fulfil their duty to provide reasons with LLM-generated reasons. It highlights the importance of human oversight and the need to design LLM-based systems in a way that enables users such as administrative decision-makers to effectively oversee them. Furthermore, the article addresses the protection of training data and trade-offs with model performance, bias prevention and explainability to highlight the need for interdisciplinary research projects.
CRIS-Team Scopus Importer:2025-02-14
Keywords: administrative decision-making; artificial intelligence (AI); automated decision-making; large language models (LLMs)

Prävention von Straftaten mit Bitcoins und Alt-Coins – Handlungsempfehlung zur Regulierung virtueller Kryptowährungen - Böhme, Rainer; Grzywotz, Johanna; Pesch, Paulina Jo; Safferling, Christoph; Rückert, Christian (2017)
Keywords: Bitcoin; Regulierung; Handlungsempfehlung

Safeguarding the evidential value of forensic cryptocurrency investigations - Rückert, Christian; Fröwis, Michael; Gottschalk, Thilo; Haslhofer, Bernhard; Pesch, Paulina J. (Forensic Science International: Digital Investigation, 2020)
Analyzing cryptocurrency payment flows has become a key forensic method in law enforcement and is nowadays used to investigate a wide spectrum of criminal activities. However, despite its widespread adoption, the evidential value of obtained findings in court is still largely unclear. In this paper, we focus on the key ingredients of modern cryptocurrency analytics techniques, which are clustering heuristics and attribution tags. We identify internationally accepted standards and rules for substantiating suspicions and providing evidence in court and project them onto current cryptocurrency forensics practices. By providing an empirical analysis of CoinJoin transactions, we illustrate possible sources of misinterpretation in algorithmic clustering heuristics. Eventually, we derive a set of legal key requirements and translate them into a technical data sharing framework that fosters compliance with existing legal and technical standards in the realm of cryptocurrency forensics. Integrating the proposed framework in modern cryptocurrency analytics tools could allow more efficient and effective investigations, while safeguarding the evidential value of the analysis and the fundamental rights of affected person
Keywords: Digital forensics; Cryptocurrencies; Digital evidence; Safeguards; Legal

Smart Border is Watching You! Fundamental Rights Implications of Automated Data Processing and Decision- Making at the EU Border - Pesch, Paulina; Boehm, Franziska (Oxford University Press, 2024)
CRIS-Team Scopus Importer:2024-12-13

The case of LAION: The first (German) court decision on text and data mining (TDM) in the context of machine learning – Comment on Regional Court of Hamburg, judgment of 27 September 2024 – 310 O 227/23 [with a machine translation of the judgment], - Pesch, Paulina (LegalTech, 2025)
The Regional Court of Hamburg has published the first German and probably also the first European court decision on text and data mining (TDM) in the context of machine learning. Albeit the decision concerns the preparation of training datasets only, the judgment addresses the broa der question of whether reproductions of works in the context of training (generative) machine learning models can be permissible under Art. 3 f. DSM Directive1 , Sections 44b, 60d of the German Copyright Act2 . A shortened machine translation of the judgment is provided below. The subse quent comment briefly introduces the relevant technical basics and discusses the court’s statements, identifying both strengths and weaknesses of the judgment. The comment discusses especially whether, and if so, to which extent machine learning training constitutes TDM within the mea ning of Art. 3 f. DSM Directive, and Sections 44b, 60d of the German Copyright Act by which the German legislator has transposed the DSM provi sions into national law. Furthermore, the comment analyses the requirement of machine-readability for rights reservations concerning online con tent. <br
Keywords: AI; Artificial Intelligence; AI training; Machine Learning; Large Language Models; LLMs; text and data mining; TDM; TDM rights reservations; machine readability